Applying muscle synergy analysis to forearm high-density electromyography of healthy people - Geng, Yanjuan; Chen, Ziyin; Zhao, Yang; Cheung, Vincent C. K.; Li, Guanglin (Frontiers in Neuroscience, 2022)
Muscle synergy is regarded as a motor control strategy deployed by the central nervous system. Clarifying the modulation of muscle synergies under different strength training modes is important for the rehabilitation of motor-impaired patients. To represent the subtle variation of neuromuscular activities from the smaller forearm muscles during wrist motion, we proposed to apply muscle synergy analysis to preprocessed high-density electromyographic data (HDEMG). Here, modulation of muscle synergies within and across the isometric and isotonic training modes for strengthening muscles across the wrist were investigated. Surface HDEMGs were recorded from healthy subjects (N=10). Three different HDEMG electrode configurations were used for comparison and validation of the extracted muscle synergies. The cosine of principal angles and the Euclidian distance between synergy vectors were used to evaluate the intra- and inter-mode similarity of muscle synergies. Then, how the activation coefficients modulate the excitation of specific synergy under each mode was examined by pattern recognition. Next, for a closer look at the mode-specific synergies and the synergies shared by the two training modes, k-means clustering was applied. We observed high similarity of muscle synergies across different tasks within each training mode, but decreased similarity of muscle synergies across different training modes. Both intra- and inter-mode similarity of muscle synergies were consistently robust to electrode configurations regardless of the similarity metric used. Overall, our findings suggest that applying muscle synergy analysis to HDEMG is feasible, and that the traditional muscle synergies defined by whole-muscle components may be broadened to include sub-muscle components represented by the HDEMG channels. This work may lead to an appropriate neuromuscular analysis method for motor function evaluation in clinical settings and provide valuable insights for the prescription of rehabilitation training therapies.